Robotics in Spine Surgery: A Technical Overview and Review of Key Concepts - Farber, S. Harrison; Pacult, Mark A.; Godzik, Jakub; Walker, Corey T.; Turner, Jay D.; Porter, Randall W.; Uribe, Juan S. (Frontiers in Surgery, 2021)
The use of robotic systems to aid in surgical procedures has greatly increased over the past decade. Fields such as general surgery, urology, and gynecology have widely adopted robotic surgery as part of everyday practice. The use of robotic systems in the field of spine surgery has recently begun to be explored. Surgical procedures involving the spine often require fixation via pedicle screw placement, which is a task that may be augmented by the use of robotic technology. There is little margin for error with pedicle screw placement, because screw malposition may lead to serious complications, such as neurologic or vascular injury. Robotic systems must provide a degree of accuracy comparable to that of already-established methods of screw placement, including free-hand, fluoroscopically assisted, and computed tomography–assisted screw placement. In the past several years, reports have cataloged early results that show the robotic systems are associated with equivalent accuracy and decreased radiation exposure compared with other methods of screw placement. However, the literature is still lacking with regard to long-term outcomes with these systems. This report provides a technical overview of robotics in spine surgery based on experience at a single institution using the ExcelsiusGPS (Globus Medical; Audobon, PA, USA) robotic system for pedicle screw fixation. The current state of the field with regard to salient issues in robotics and future directions for robotics in spinal surgery are also discussed.